Official data on German water supply: 2004, 2007, 2010; Statistik über die öffentliche Wasserversorgung: 2004, 2007, 2010 - Michael Zschille (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The Research Data Centers of the German Federal Statistical Office and the Statistical Offices of the German 'Länder' provide information on potable water supply in Germany ('Statistik der öffentlichen Wasserver- und Abwasserentsorgung', EVAS No. 32211). Together with these statistics, information on sewage collection and treatment is also available. However, the focus of this data documentation is only on the data on potable water supply. [...]
Keywords: 330